PENYIDIKAN TINDAK PIDANA NARKOTIKA DALAM LINGKUP PERADILAN MILITER (Studi terhadap Peran Polisi Militer Kodam Angkatan Darat Dalam Penyidikan Tindak Pidana Narkotika Dikalangan TNI Angkatan Darat, Pomdam III/Siliwangi) - Firdaus Arief Chandra (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2012)
In writing this paper the author discusses the Narcotics Crime Investigation In Scope of MilitaryJustice , which focuses on the role of the military command of the Army Military Police InNarcotics Investigation Crime Amongst the Army Pomdam III / Siliwangi.It is against the backdrop that in a military unit , especially with regard to service members whoseactions violate the law, a unified commander has a duty and responsibility to establish, followand take legal measures in accordance with the duties and responsibilities of authority. As acommander of the environment. TNI certainly demanded its role in fostering subordinatesoldiers, according to the authority provided for in article 69 of Law No. 31 of 1997 is as BossesPunish Eligible as an investigator. Where a unit commander or supervisor who has the right topunish the implementation assisted by Military Police investigators within the military as well asit is followed up by the Military Judge Advocate and a unified commander has two principal orprimary function, namely as a supervisor who has the right to punish ( ANKUM ) and submittersofficer case ( Papera ). Military Police in carrying out its duties and functions as an investigator isoften met with resistance, especially during the interrogation of narcotic crime that occurred inthe Army.The purpose of the research is the first to describe and analyze the process of criminalinvestigations conducted by the Police Narcotics Military Military Command of the Army, thesecond to describe and analyze the factors that cause the abuse of narcotics in the TNI- AD andthe third to describe and analyze the legal obstacles that occur in the investigation of criminaloffenses that occur in the environment narcotics Army.In this thesis the approach used is the juridical empirical research that examines the juridical andempirical aspects of criminal investigations within the military justice Narcotics by MilitaryPolice Army Military Command Bandung on juridical aspects in the study conducted on theprocedures applicable regulations , and coupled with the literature obtained through the booksrelating to the role of the Military Police military Command Army narcotic in the investigation ofcriminal offenses within the scope of military justice . While aspects of the empirical approach tothe locus of action in the Military Police Force Military Command DaratkotaBandung ininvestigating acts pidanaNarkotika.The results of research conducted on the stage of the investigation process is conducted militarypolice on narcotic cases occur among members of the army are : First , each of the investigationsconducted by Pomdam III / SLW, Danpomdam / Wadanpomdam will give direct orders to thesection investigations led by executing investigation unit commander rank of Captain and in itthere are four and five non-commissioned officer who served as inspector executor investigation. In the event of an act which is considered as an unlawful act committed by Army soldiersonkum in particular , the community or the police to give his report to Pomdam III / SLW overwhat is witnessed, known and experienced. After that it will go to the location Pomdam reportedto perform reconnaissance for approximately one week of receiving a report is received. If it isnot there some irregularities during the reconnaissance reconnaissance will be discontinued dueto lack of evidence obtained and when it is alleged that during reconnaissance proved true, thenthe next process is to conduct raids and arrests in place. Furthermore, the army officers who werecaught in the raid will be brought to Pomdam III / SLW to undergo interrogation and search,within 1x24 hour urine examination should have been made to the local health department thathas been designated by the Ministry of Health. Narcotics evidence subsequently obtained withinthree days had to be submitted to the Laboratory ( Lab ) designated Center for Food and DrugAdministration ( POM ) and subsequently the National Narcotics Agency ( BNN ) whichdetermines the outcome of the POM hall is included in the type of narcotics or not. After allchecks are undertaken , then made a legal opinion letter of suggestions made by trial counsel thensubmitted to Papera that will make Sekeptera letter to do the trial . If the decision of the judge inthe trial verdict of guilt to the perpetrators, the perpetrators will be put into prisons ( prisons )Kebun Waru or prisons designated by the military court. For a contributing factor, there are 3factors ( reasons ) that can be regarded as a "trigger " a person in a drug penyalahgunakantakterkecuali also be a factor as a member of the Army abusing drugs . The third factor is thefactor of self , environmental factors , and factors willingness drug itself. Obstacles encounteredin the Army Military Police criminal investigations involving narcotics TNI - AD is the processof law enforcement at the level of investigation and prosecution has been no transparency, yetintegrated case management system in the military environment , human resources are limited,facilities and infrastructure insufficient, the supervisory function of the quality of decisions andthe conduct of judges is not optimal , and software that is not in harmony with law enforcementpratek.Keywords : investigation , military police , narcotic crime